دور التدريب عن بعد في تحسين الكفاية المهنية لدى المعلمين من وجهة نظر معلمات المرحلة الأساسية في محافظة الزرقاء - العواملة، رائدة علي عبدالكريم (الجامعة الإسلامية بغزة - شئون البحث العلمي والدراسات العليا, 2023)
هدفت الدراسة التعرف إلى دور التدريب عن بعد في تحسين الكفاية المهنية لدى المعلمين من وجهة نظر معلمات المرحلة الأساسية بمحافظة الزرقاء في الأردن، تم اعتماد المنهج الوصفي المسحي، والاستبانة، وتكونت عينة الدراسة من (173) معلمة، وأظهرت نتائج الدراسة أن دور التدريب عن بعد في تحسين الكفاية المهنية لدى المعلمين من وجهة نظر معلمات المرحلة الأساسية جاء ضمن المستوى المتوسط بمتوسط حسابي بلغ (3.60)، وأن درجة سبل تحسين دور التدريب عن بعد في تحسين الكفاية المهنية لدى المعلمين من وجهة نظر المعلمات جاءت ضمن المستوى المرتفع بمتوسط (3.82)، وكانت أكثر سبل تحسين دور التدريب عن بعد في تحسين الكفاية المهنية لدى المعلمين من وجهة نظر المعلمات للمرحلة الأساسية أن تتناسب المدة الزمنية للتدريب عن بعد مع مسؤوليات المعلم نفسه، ووجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α ≤ 0.05) بين متوسطات استجابات العينة حول دور التدريب عن بعد في تحسين الكفاية المهنية لدى المعلمين من وجهة نظر معلمات المرحلة الأساسية تعزى لمتغير المؤهل الأكاديمي، وكانت تلك الفروقات لصالح الحاصلين على درجة الدكتوراه، وعدم وجود فروق تعزى لمتغير سنوات الخبرة، ووجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α ≤ 0.05) بين متوسطات استجابات العينة حول سبل تحسين دور التدريب عن بعد في تحسين الكفاية المهنية لدى المعلمين تعزى لمتغير المؤهل الأكاديمي، وكانت الفروقات لصالح الحاصلين على درجة الدكتوراه، ولمتغير سنوات الخبرة لصالح من لديهم خبرة من (5 -10) سنوات، أوصت الدراسة بضرورة تنمية الكفاية المهنية للمعلمين باستخدام التدريب عن بعد. The study aimed to identify the role of distance training in improving the professional competence of teachers from the point of view of the primary stage teachers in Zarqa Governorate in Jordan. The descriptive survey method and the questionnaire were adopted, and the study sample consisted of (173) female teachers. Improving the professional competence of teachers from the point of view of the female teachers of the basic stage came within the intermediate level with an arithmetic average of (3.60), and that the degree of ways to improve the role of distance training in improving the professional competence of teachers from the point of view of the female teachers came within the high level. With an average of (3.82), the most important ways to improve the role of distance training in improving the professional competence of teachers from the point of view of the female teachers for the basic stage were: The time period for distance training should be commensurate with the responsibilities of the teacher himself, and there are statistically significant differences at the level of significance (α ≤ 0.05) between the averages of the sample’s responses about the role of distance training in improving the professional competence of teachers from the point of view of the basic stage female teachers due to the variable of academic qualification, and those differences were in favor of those with a doctorate degree, and there were no differences due to the variable years of experience, and there were statistically significant differences At the level of significance (α ≤ 0.05) between the average responses of the sample about ways to improve the role of distance training in improving the professional competence of teachers from the point of view of the primary stage teachers, it is attributed to the academic qualification variable, and those differences were in favor of those with a doctorate degree, and the variable years of experience, and they were These differences are in favor of those with (5-10) years of experience, The study recommended the importance of developing the professional competence of teachers using distance training
Keywords: التدريبات الإلكترونية -- الكفايات التدريسية -- التعليم الأساسي -- المدارس الأردنية